Measurement and Control of an Incubator Temperature by Using Conventional Methods and Fiber Bragg Grating (FBG) Based Temperature Sensors. - Burunkaya, Mustafa; Yucel, Murat (Journal of Medical Systems, 2020)
Incubator is a medical device that provide a climatic environment for a newborn and a preterm infant. In the incubator environment, especially, the temperature significantly increases the survival rate of infants. In this study, the incubator air temperature, temperature uniformity and infant skin temperature were measured and controlled with conventional methods and FBG based temperature sensors, and their results and related literature results were compared among them. To this end, in addition to classical sensors, six FBG sensors were used during the measurements, and very close results were obtained between them (R2 = 0.9989). In addition, since real time monitoring of the FBG bands were ensured with a user-friendly interface, measurement processes have been made more ergonomic. In this way, the insulation required for the measurements is also provided perfectly. Measurement errors caused by conventional sensors' properties, which are different for each of them, change over/with time, and also change with different values, have been minimized by using this method. Moreover, in case of increasing the number of sensors for multi-point, continuous and real time temperature measurement in conventional methods, some of the problems such as monitoring of these sensors, obstructing or changing the air flow due to the confusions of these sensors and their cables in the incubator cabinet, and following these, control errors caused by these reasons, and difficulties that may be happened during the infant care and resuscitation procedures have been eliminated. Thus, thermoneutrality in closed incubators were also able to validated and assessed fast and more accurately for preterm and neonates.